Prospective study of gait function before and 2years after total knee arthroplasty - Kramers-de Quervain, Inès A.; Kämpfen, Stéphane; Munzinger, Urs; Mannion, Anne F. (The knee, 2012)
To perform a prospective evaluation of gait before and 2years after total knee arthroplasty (TKA) and examine the influence of comorbidity and other joint problems on gait characteristics and their improvement after TKA. One hundred and eleven patients scheduled for TKA took part (34 men, 65±10y; 77 women, age 68±9y). Gait velocity, cadence, and ground reaction force parameters were measured before and 2years after surgery. Patients completed a questionnaire to rate their pain and other joint problems. Comorbidity was measured with the American Society of Anaesthesiologists (ASA) score. Two years after TKA there were significant improvements (each p<0.05) in gait velocity and cadence and most of the ground reaction parameters, though forces during loading/unloading remained lower for the operated leg than for the contralateral leg. Higher comorbidity and other painful joints of the lower extremities/spine had a consistent, negative influence (p<0.05) on the absolute values achieved for the gait parameters although their improvement compared with baseline was independent of these factors. Comorbidity and other joint problems negatively influenced gait performance. These confounders should be taken into account when setting realistic patient expectations and when interpreting the success of TKA in the individual patient. Improvement in gait is however still possible, within the bounds of concomitant comorbidity.